PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 15 PADANG - Hutri Rozalia (Jurnal Edukasi dan Penelitian Matematika, 2018)
This study aims to find out the understanding of mathematical concepts students learn by using Model Cooperative Learning Numbered Heads Together type is better than the understanding of mathematical concepts students learn by using conventional learning in class VIII SMPN 15 Padang. Type of research is Quasi-Experimental Research with the study design static  group  design. The study population  was students of  class  VIII SMPN 15 Padang.  Sampling techniques was random sampling, assigned to class VIII.7 as the experiment class and class VIII.6 as the control class. Instrument of research  is a final test of students' understanding of mathematical concepts. Data analysis used U Mann Whitney test. Based on the data analysis test of understanding of mathematical concepts, obtained P-value = 0.0466 less than the 0,05 significance level. So it can be concluded that the understanding of mathematical concepts students learn  by using Model Cooperative Learning Numbered Heads Together type   is better than  the understanding  of mathematical concepts students learn by using conventional learning. Thus, it can be said that there is influence of cooperative learning model Numbered Heads Together type to understanding mathematical concepts of students.Keywords : Understanding of Mathematical Concept, Numbered Heads Together, Conventional Learning